Examination and evaluation of pharmaceutical designed and made patent applications for gene therapy - SEZER, ALİ DEMİR (MARMARA UNIV, FAC PHARMACY, 2016)
In recent years, one the most popular subjects of drug biotechnology is gene therapy products. When Human Genome Project was accomplished, accessing to desired genes became so much easier and this data brought a new perspective to various diseases; such as better diagnostic vehicles, protective measures and therapeutic methods. Thus, with the purpose of early patent protection of DNA-based drugs and vaccines, there have been thousands of patent applications in this area so far. These developments have brought various discussions about potential negative effects of DNA patents on innovation, right access to therapy and ethical issues and caused conflicts particularly in diagnostic field and brought to courts. For now, approved gene products for medication are extremely limited numbers and a great majority of studies are in clinical trial phase. However, gene therapy is promising for critical diseases such as cancer, cardiovascular system, autoimmune, infectious diseases, neurological and genetical disorders. In this research,, we collect data about the gene therapy products licensed and applied for patent protection; particularly their types, application methods and areas of usage. Then, in the light of case reports, national/international patent regulations and current applications, the scope and boundaries of protection provided by gene patents are analyzed and effects of this situation to public health, research area, economy and ethical approach are discussed.
Keywords: Gene therapy; DNA sequence; patent; intellectual property